Larvicidal activity of β-asarone and Acorus calamus Linn. (sweet flag) extract against Aedes aegypti (Dipotera: Culicidae): Enzyme inhibition, midgut histopathology, and in silico analysis - Subahar, Rizal; Dwira, Surya (UI Scholars Hub, 2026)
Aedes aegypti (Diptera: Culicidae), the primary vector of dengue, poses a significant public health threat in tropical and subtropical regions. Botanical insecticides and phytochemicals such as β- asarone, derived from essential oils,offer a promising alternative to synthetic larvicides. The rhizome of Acorus calamus L. (sweet flag), traditionally known for its neuroprotective and antioxidant properties, contains β-asarone as its principal bioactive constituent.This study evaluated the larvicidal efficacy of β-asarone and A. calamus rhizome extract against Ae. aegypti larvae, focusing on detoxification enzyme inhibition, midgut histopathology, and in silico molecular interactions.Third- and fourth-instar larvae were exposed to β-asarone and crude extract at concentrations ranging from 0.25 to 24.25 μg/mL. Larval mortality was recorded at 24, 48, and 72 hours post-exposure following WHO guidelines. Activities of acetylcholinesterase (AChE), glutathione-S-transferase (GST), and oxidase were measured using biochemical assays. Midgut histopathological changes were assessed via hematoxylin and eosin staining. Molecular docking (CB-Dock2) was used to evaluate β-asarone interactions with AChE, GST, and oxidase. β-asarone showed significantly higher larvicidal potency (LC₅₀ = 6.768 μg/mL) than the crude extract (LC₅₀ = 54.566 μg/mL). Both treatments markedly inhibited AChE and oxidase and caused extensive midgutdamage, including epithelial degeneration, ruptured peritrophic membrane, and loss of microvilli. These results demonstrate the potential of β-asarone as plant-derived larvicides acting through enzymatic inhibition and midgut disruption, offering a promising strategy for mosquito control.